Extracellular microRNA-21 and microRNA-26a increase in body fluids from rats with antigen induced pulmonary inflammation and children with recurrent wheezing. Issue 1 (December 2016) - Jiang, Congshan; Yu, Hongchuan; Sun, Qingzhu; Zhu, Wenhua; Xu, Jing; Gao, Ning; Zhang, Rui; Liu, Li; Wu, Xiaoying; Yang, Xudong; Meng, Liesu; Lu, Shemin
Abstract Background This study aims to find out whether extracellular miRNAs is implicated in recurrent childhood wheezing with asthmatic risk. Methods One hundred and forty children of Chinese Han population were recruited for this study. Plasma and intracellular miRNAs from children with recurrent wheezing and rats with antigen induced pulmonary inflammation (AIPI) were detected by using reverse transcription-quantitative PCR. Differential leukocytes in blood were automatically counted. Total IgE was detected by enzyme-linked immunosorbent assay. Clinical implication in diagnosis was evaluated using receiver operating characteristic curves. Results The increase of plasma miR-21 and miR-26a was screened out from 11 candidate miRNAs and validated in wheezing children. The level of expression for both miRNAs were comparable in different age and gender. Plasma miR-21 was more preferable to miR-26a and total IgE for diagnosis. Plasma miR-21 and miR-26a levels were not significantly correlated with various leukocyte counts or miRNA expression in blood cells. In acute and chronic AIPI rats, miR-21 levels increased in both plasma and lavaged lung compared with control. Moreover, circulating miR-21 and miR-26a levels were highly positively correlated with infiltrated cell counts in bronchoalveolar lavage fluid of AIPI rats. Conclusions Circulating miR-21 and miR-26a increase in wheezing children and AIPI rats. This not only manifests their strong clinical implication in recurrent childhood wheezing with asthma risk, but also provides novel insights into the role of extracellular miRNAs during development of airway inflammation and recurrent wheezing.